A Fast Radio Burst in a Compact Galaxy Group at z ∼ 1 - Gordon, A.C.; Fong, W.F.; Simha, S.; Dong, Y.; Kilpatrick, C.D.; Deller, A.T.; Ryder, S.D.; Eftekhari, T.; Glowacki, Marcin; Marnoch, L.; Muller, A.R.; Nugent, A.E.; et al. (2024)
FRB 20220610A is a high-redshift fast radio burst (FRB) that has not been observed to repeat. Here, we present rest-frame UV and optical Hubble Space Telescope observations of the field of FRB 20220610A. The imaging reveals seven extended sources, one of which we identify as the most likely host galaxy with a spectroscopic redshift of z = 1.017. We spectroscopically confirm three additional sources to be at the same redshift and identify the system as a compact galaxy group with possible signs of interaction among group members. We determine the host of FRB 20220610A to be a star-forming galaxy with a stellar mass of ≈109.7 M ⊙, mass-weighted age of ≈2.6 Gyr, and star formation rate (integrated over the last 100 Myr) of ≈1.7 M ⊙ yr−1. These host properties are commensurate with the star-forming field galaxy population at z ∼ 1 and trace their properties analogously to the population of low-z FRB hosts. Based on estimates of the total stellar mass of the galaxy group, we calculate a fiducial contribution to the observed dispersion measure from the intragroup medium of ≈90-182 pc cm−3 (rest frame). This leaves a significant excess of 515 − 272 + 122 pc cm−3 (in the observer frame); further observation will be required to determine the origin of this excess. Given the low occurrence rates of galaxies in compact groups, the discovery of an FRB in one demonstrates a rare, novel environment in which FRBs can occur. As such groups may represent ongoing or future mergers that can trigger star formation, this supports a young stellar progenitor relative to star formation.